2019
DOI: 10.1038/s42255-019-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Reverse gene–environment interaction approach to identify variants influencing body-mass index in humans

Abstract: Identifying gene-environment interactions (GxEs) contributing to human cardiometabolic disorders is challenging. Here we apply a reverse GxE candidate search by deriving candidate variants from promoter-enhancer interactions that respond to dietary fatty acid challenge through altered chromatin accessibility in human primary adipocytes. We then test all variants residing in the lipid-responsive open chromatin sites within adipocyte promoter-enhancer contacts for interaction effects between the genotype and die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…LDB3 was well known for its role in myofibrillar myopathies. Recent study found that the LDB3 promoter responds to lipid uptake in human adipose tissue [ 57 ]. AIF1L protein seemed to exist in all adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…LDB3 was well known for its role in myofibrillar myopathies. Recent study found that the LDB3 promoter responds to lipid uptake in human adipose tissue [ 57 ]. AIF1L protein seemed to exist in all adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter Capture Hi-C assay was performed using two replicates of 10 million HepG2 cells, as described previously. 25 The libraries were sequenced on the Illumina HiSeq 4000 platform. On average, 114.4 M paired-end reads were obtained per sample.…”
Section: Promoter Capture Hi-c Library Preparation and Data Processingmentioning
confidence: 99%
“…Beyond germ-like mutations that may predispose to disease, which has largely been the focus of genetic studies in NAFLD, heritable epigenetic changes also have an important role in NAFLD-associated HCC which include but are not limited to DNA methylation, chromosomal looping interactions, RNA modifications and the emerging role of non-coding RNAs [ 54 57 ] . Additionally, several studies have applied circulating tumor DNA (cfDNA) methods to further study HCC [ 58 , 59 ] , which has not only shed some light on the biology of HCC but is also promising for use as a biomarker in the future.…”
Section: Genetic Risk Factors For Nafld-hccmentioning
confidence: 99%
“…Additionally, several studies have applied circulating tumor DNA (cfDNA) methods to further study HCC [ 58 , 59 ] , which has not only shed some light on the biology of HCC but is also promising for use as a biomarker in the future. The identification of these epigenetic modifications points to further understanding of gene regulation changes, which are influenced by their environment [ 54 ] .…”
Section: Genetic Risk Factors For Nafld-hccmentioning
confidence: 99%
See 1 more Smart Citation